EFISIENSI REPRODUKSI KAMBING PERANKAN ETAWA DI LEMBAH GOGONITI FARM DI DESA KEMIRIGEDE KECAMATAN KESAMBEN KABUPATEN BLITAR - Edya Moelia Lubis (Universitas Islam Balitar, 2016)
The purpose of this research is to know the level of reproduction efficiency through Conception Rate (CR), Service per Conception (S / C), Days Open (DO), and Kidding Interval (KI) in Kemirigede Village Kesamben District, Blitar Regency. The usefulness of this research is as a guideline for goat breeders in improving livestock raising management, adding insight on the importance of knowing CR, S / C, DO and KI and as a reference of the breeders for goat breeding especially in reproduction efficiency. The research material was Etawa females 35 female heads. The method used is survey method, while the selection of livestock sample is done by purposive sampling. Data analysis using descriptive analysis. The research results of Etawa Peranakan Goats in Lembah Gogoniti Farm Desa Kemirigede Kesamben Subdistrict of Blitar District showed that CR value was 85%, S / C 2.5 years 1 time, age 3 years 1 time and age 5 years 1.41 times, KI age 2.5 years 6.49 months, age 3 years 6.56 months, age 4 years 6,81 months and age 5 years 7.04 months and DO age 2.5 years 44 days, age 3 years 46.8 days , age 4 years 53.75 days and age 5 years 60.5 days. The conclusions of this study are the RC, S / C, KI and DO values according to the standard (for Conception Rate of at least 60%, Service per Conception 1.0 - 2.0, 9 Months Kidding Interval and 90 Days Open Days). Suggested breeders not only refers to the CR system, but also on the system S / C, KI and DO so that will get optimal results.Keywords: Production Efficiency, Conception Rate, Days Open